Penggunaan Aplikasi Tiktok sebagai Media Pemasaran Pof Perfume - Mohammad Fawaid Pradika; Sumardjijati Sumardjijati (Journal on Education, 2023)
Tiktok is a new social media launched in 2016, there are many active users of Tiktok in Indonesia, so the use of Tiktok as a marketing channel is one of the right strategies. POF Perfume as brand sees this opportunity, and utilizes Tiktok to become a marketing medium so as to get fantastic sales of 35 thousand products since January 2022. The purpose of this research is to find out how Tiktok is used as a marketing medium for POF Perfume. The research method used is descriptive qualitative by interviewing the management and consumers of POF Perfume. The results of this study indicate that the use of the duration video feature, live streaming feature, TiktokShop feature with the AISAS model is carried out optimally which results in an increase in the intended sales. Management needs to optimize the stories as a marketing communication tool, and maximize the use of TiktokAds